Any Sugar with That? Assessment of Dissolved Sucrose as Supplementary Feed in Nursery Rearing of Juvenile Bivalves - Andy Jordan; Bradley Skelton; Maria Mugica; Andrew Jeffs (Fishes)
The costly production of live microalgal feed prevents the inclusion of an extended nursery phase in bivalve aquaculture. One method of feeding juvenile bivalves that has received minimal attention is the use of dissolved nutrients to reduce the reliance on live microalgae as a sole feed input. This study aimed to determine whether dissolved sucrose could work as a supplement to live microalgae. Two different concentrations of dissolved sucrose (i.e., 100 μg mL−1 and 1 mg mL−1) were each provided daily for 2 h and 4 h to juvenile Greenshell™ mussels as a supplement to a diet of live microalgae. The growth and survival of the mussels were measured over three weeks. All combinations of sucrose concentrations and exposures improved the growth of spat compared with the control without sucrose. However, the best-performing spat were provided with a concentration of 1 mg mL−1 of dissolved sucrose for an exposure time of 4 h, which induced 57% greater spat growth daily compared with the control diet. The mussel spat supplemented with dissolved sucrose also accumulated greater carbohydrate content compared with those in the control treatment, indicating they were in greater nutritional condition. This demonstration that dissolved sucrose can significantly improve the growth and nutritional composition of mussel spat over periods as short as 2 h shows promise for the commercial application of sucrose as low-cost supplementary feed in bivalve nurseries.